Answer:
Step-by-step explanation:
X intercept is where the line crosses the x axis or where y=0
y intercept is where the line crosses the y axis or where x=0
so
6x-3y=-6
x intercept
y=0
6x-3(0)=-6
6x=-6
x=-1
x intercept at x=-1 or the point (-1,0)
y intercept
x=0
6(0)-3y=-6
-3y=-6
y=2
y intercept at y=2 or the point (0,2)
First off, do a prime factoring of the constant and leading coefficient, namely 9 and 8 respectively.
so a prime factoring of 8 is 2*2*2, and a prime factoring of 9 is 3*3.
so, those are the factors... now, how do we produce products that gives us the middle coefficient +18?
well, let's see hmmmm 2 * 3 * 3 and 2 * 3....so that's 18 + 6, that's 24.. .so... no good is not 18, let's try again.
2*2*3 and 2 * 3, so that's 12 + 6, now, that's +18
so we'll use those, 2*2*3 and 2*3, or 4 * 3 an 2 * 3, (4x + 3)(2x + 3) = 0.
Answer:
x = 1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
4x−
5
5
=3
4x+−1=3
4x−1=3
Step 2: Add 1 to both sides.
4x−1+1=3+1
4x=4
Step 3: Divide both sides by 4.
4x
4
=
4
4
x=1
Answer:
y = 2
Step-by-step explanation:
-2y + 1 = y-5
-2 - y = -5 - 1
-3y = -6
y = -6 ÷ -3
y = 2